The tobacco-specific carcinogen NNK induces pulmonary tumorigenesis via nAChR/Src/STAT3-mediated activation of the renin-angiotensin system and IGF-1R signaling - Hye-Jin Boo; Hye-Young Min; Su Jung Hwang; Hyo-Jong Lee; Jae-Won Lee; Sei-Ryang Oh; Choon-Sik Park; Jong-Sook Park; You Mie Lee; Ho-Young Lee (Experimental and Molecular Medicine, 2023)
Abstract The renin-angiotensin (RA) system has been implicated in lung tumorigenesis without detailed mechanistic elucidation. Here, we demonstrate that exposure to the representative tobacco-specific carcinogen nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) promotes lung tumorigenesis through deregulation of the pulmonary RA system. Mechanistically, NNK binding to the nicotinic acetylcholine receptor (nAChR) induces Src-mediated signal transducer and activator of transcription 3 (STAT3) activation, resulting in transcriptional upregulation of angiotensinogen (AGT) and subsequent induction of the angiotensin II (AngII) receptor type 1 (AGTR1) signaling pathway. In parallel, NNK concurrently increases insulin-like growth factor 2 (IGF2) production and activation of IGF-1R/insulin receptor (IR) signaling via a two-step pathway involving transcriptional upregulation of IGF2 through STAT3 activation and enhanced secretion from intracellular storage through AngII/AGTR1/PLC-intervened calcium release. NNK-mediated crosstalk between IGF-1R/IR and AGTR1 signaling promoted tumorigenic activity in lung epithelial and stromal cells. Lung tumorigenesis caused by NNK exposure or alveolar type 2 cell-specific Src activation was suppressed by heterozygous Agt knockout or clinically available inhibitors of the nAChR/Src or AngII/AGTR1 pathways. These results demonstrate that NNK-induced stimulation of the lung RA system leads to IGF2-mediated IGF-1R/IR signaling activation in lung epithelial and stromal cells, resulting in lung tumorigenesis in smokers.